An integrated study (inoceramid bivalves, ammonites, calcareous nannofossils, planktonic foraminifera, stable carbon isotopes) of the Ten Mile Creek section, Lancaster, Dallas County, north Texas, a candidate Global boundary Stratotype Section and Point - Gale, Andy; Kennedy, W.; Lees, J.; Petrizzo, M.; Walasczcyk, I. (2007)
The WalMart section on Ten Mile Creek, Lancaster, Dallas County, Texas, exposes a 23 metre section of Austin Chalk that can be integrated into a more than 60 m composite sequence for the Dallas area on the basis of bed-by-bed correlation. The section was proposed as a possible candidat e Global Boundary Stratotype at the 1995 Brussels meeting on Cretaceous Stage boundaries, with the first occurrence of the inoceramid bivalve Cladoceramus undulatoplicatus (ROEMER, 1852) as the potential boundary marker. An integrated study of the inoceramid bivalves, ammonites, planktonic foraminifera, and calcareous nannofossils places the first occurrence of Cl. undulatoplicatus in a matrix of ten ancillary biostratigraphic markers. The candidate Global boundary Stratotype Section and Point (GSSP) is located within a composite stable carbon isotope curve for the Austin Chalk as a whole. This shows it to lie 3.5 m below the Michel Dean stable carbon isotope event, originally recognised in the English Chalk. The first occurrence of Cl. undulatoplicatus lies in the same position in relation to stable carbon isotope events in both Texas and England that can in principle be recognised globally in marine sediments. The WalMart section satisfies many of the criteria required of a GSSP for the base of the Santonian Stage, although ownership and access require clarification.